The Effect of Perceived Knowledge of Accounting, Business Scale, and Level of Education Level of MSME Actors Against Use of Accounting Information in Palembang City - Permana, Eko; Trisninawati, Trisninawati (International Journal of Finance Research, 2024)
This study aims to determine the effect of perceived accounting knowledge, business scale, and education level of MSME actors on the use of accounting information in Palembang City. The research method used is descriptive quantitative. The data used in the study were primary data and secondary data. The sampling technique used non- probability sampling techniques. The sample studied in this study were 100 respondents who were MSMEs in Palembang City, especially the Plaju and Kertapati areas. Based on the statistical t test conducted, it can be concluded that the perception of accounting knowledge affects the use of accounting information with a significance value of 0.000 <0.05. Based on the statistical t test conducted, it can be concluded that the scale of business has no effect on the use of accounting information 0.438> 0.05. Based on the statistical t test conducted, it can be concluded that the level of education affects the use of accounting information with a significance value of 0.000 <0.05. The magnitude of the influence of the independent variable on the dependent variable is 50.8%, the remaining 49.2% is influenced by other variables that are not included in the research model.